Seed and bud banks respond differentially to seasonal flooding disturbance along a successional gradient in a river-connected floodplain wetland - Wen-jing Sun; Shu-qiong Wang; Xing-hui Lu; Jia-shun Zhong; Xin-zhi Guo; Xin-sheng Chen (Global Ecology and Conservation)
Soil seed banks and belowground bud banks play crucial roles in population recruitment and vegetation succession in wetlands. Successional stages and flooding disturbance influence seed and bud bank traits but have rarely been explored in floodplain wetlands. We investigated seed and bud banks species composition and density along a successional gradient from shallow water to Carex grassland in Shengjin Lake—a floodplain wetland of the Yangtze River in China—before (May 2023) and after (November 2023) flooding. The species richness of soil seed banks and species similarity with extant communities increased from shallow water to Carex grassland before and after flooding. The few species in bud banks were perennial macrophytes, namely, Carex thunbergii, Phalaris arundinacea, and Eleocharis valleculosa var. setosa. The density of soil seed banks increased from shallow water, mudflat, to Carex grassland (6980, 9438, and 18,140 seeds m-2, respectively) before flooding and significantly decreased after flooding (3174, 7608, and 10,439 seeds m-2, respectively). The density of the bud bank increased from shallow water, mudflat, to Carex grassland (0, 78, and 437 buds m-2, respectively) before flooding but significantly increased after flooding in shallow water and Carex grassland (16 and 1082 buds m-2, respectively). Our results indicated that both seed and bud banks increased across the successional gradient from shallow water to Carex grassland and responded differently to seasonal flooding except that bud banks in mudflat showed similar response trends. Therefore, vegetation restoration in floodplain wetlands should consider the interplay between seed and bud banks, successional stage, and flooding disturbance.